Роль комплексу маркетингу у формуванні логістичної системи підприємства - Савченко, Т.В.; Загора, Р.В. (Економічний вісник Донбасу, 2025)
У статті встановлено взаємозв’язок між комплексом маркетингу та логістичною системою підприємства. Досліджено теоретичні підходи до визначення поняття «логістична система» та надано її ключові характеристики. Показано, що логістичний підхід до управління матеріальними потоками базується на системності, інтеграції та узгодженості дій усіх структурних елементів підприємства. Увагу зосереджено на концепції маркетингової логістики, яка об'єднує стратегічні інструменти маркетингу (8P) з операційними механізмами логістики для досягнення високого рівня сервісу та ефективності. Обґрунтовано, що логістика не функціонує автономно, а виступає продовженням маркетингових процесів, реалізуючи сформовану маркетингом ринкову пропозицію через ефективну організацію матеріальних, інформаційних та фінансових потоків. Визначено, що взаємодія між логістикою та маркетингом має двосторонній характер: маркетинг формує попит і вимоги до логістичних операцій, а логістика, у свою чергу, впливає на обмеження й можливості маркетингових стратегій. Розкрито доцільність зміни традиційної логіки логістичних процесів у напрямі зворотного планування: від споживача до постачальника. Запропоновано модель оберненої логіки організації потоків для врахування впливу маркетингових інструментів на окремі підсистеми логістичної системи. The article establishes the interrelation between the marketing mix and the enterprise’s logistics system. It examines theoretical approaches to the definition of the term "logistics system" and outlines its key characteristics. Logistics, as an integrated organizational and economic system, ensures effective flow management aimed at meeting consumer needs with minimal costs. Its efficiency largely depends on coordinated interaction with marketing, which generates demand and defines customer service parameters. It is demonstrated that the logistics approach to material flow management is based on systematization, integration, and coherence of actions across all structural elements of the enterprise. Special attention is given to the concept of marketing logistics, which combines strategic marketing tools (8P) with operational logistics mechanisms to achieve high service levels and operational efficiency. The study argues that logistics does not function autonomously but continues marketing processes, implementing market offers through the effective organization of material, informational, and financial flows. It is determined that the relationship between logistics and marketing is bidirectional: marketing shapes demand and defines requirements for logistics operations, while logistics, in turn, imposes constraints and influences marketing strategy capabilities. The research emphasizes marketing's crucial role in shaping the enterprise’s logistics system by initiating and coordinating its development, ensuring strategic alignment across all stages of product movement – from product design to final delivery. The relevance of reversing the traditional logistics process logic – from consumer to supplier – is substantiated. A model of reverse flow organization is proposed to incorporate marketing tools' influence on specific logistics system subsystems. The necessity of strategic integration between logistics and marketing functions into a unified management system is highlighted, enabling flexible responses to market dynamics and ensuring sustainable enterprise development.